Imaging and Clinical Outcomes in 20 Dogs Treated with Thin Film Banding for Extrahepatic Portosystemic Shunts. Issue 6 (8th July 2016) - Nelson, Nathan C.; Nelson, Laura L.
Abstract : Objective: To prospectively evaluate the efficacy of thin film band attenuation of congenital extrahepatic portosystemic shunts (CEPSS) in dogs using clinical, biochemical, and imaging‐related outcome measures. Study Design: Prospective case series. Animals: Dogs with CEPSS (n=20). Methods: Client‐owned dogs with CEPSS were enrolled and thin film banding of the shunting vessel was performed. Before and at least 6 months after surgery, serum bile acids and computed tomography (CT) angiography were performed and owners completed a health questionnaire regarding the dog's clinical signs. Postoperative CT images were assessed for the effectiveness of band closure, change in portal vein/aorta ratio, change in liver volume/weight ratio, and whether the band was placed in the appropriate location. Preoperative and postoperative health questionnaire data and serum bile acids were compared. Results: The band resulted in complete closure of the vessel around which it was placed in 13 dogs. In the remaining 7 dogs, the vessel lumen was narrowed but not completely closed. In 8 dogs the band location was suboptimal, allowing systemic drainage of visceral blood or secondary shunting branches to persist. Liver volume/body weight ratios and portal vein/aorta diameter ratios increased in most dogs. Serum bile acids decreased in all but 1 dog and owners reported improved health in 19 dogs. Conclusion: Thin film banding resulted in complete occlusion of many, but not all vessels around which it was placed. Even in dogs with inappropriate band location or with incomplete closure, clinical improvement can be expected based on our results.